LTBK-01. INO-5401 AND INO-9012 DELIVERED INTRAMUSCULARLY (IM) WITH ELECTROPORATION (EP) IN COMBINATION WITH CEMIPLIMAB (REGN2810) IN NEWLY DIAGNOSED GLIOBLASTOMA. (20th November 2020) - Reardon, David A; Brem, Steven; Desai, Arati Suvas; Bagley, Stephen Joseph; Kurz, Sylvia Christine; De La Fuente, Macarena Ines; Nagpal, Seema; Welch, Mary Roberta; Hormigo, Adilia; Forsyth, Peter; Mandell, Jacob; Khagi, Simon; et al.
Abstract: BACKGROUND: Novel T cell-enabling therapies, in combination with checkpoint inhibition, may improve OS in GBM. INO-5401 (synthetic DNA plasmids encoding hTERT, WT-1, PSMA) plus INO-9012 (synthetic DNA plasmid encoding IL-12), and the PD-1 immune checkpoint inhibitor cemiplimab, is given to patients with newly diagnosed GBM to evaluate tolerability, efficacy and immunogenicity. METHODS: Phase I/II, single arm, 2 cohort study (A: MGMT unmethylated, B: MGMT methylated). Primary endpoint is safety; efficacy and immunogenicity are secondary. Nine mg INO-5401 plus 1 mg INO-9012 (every 3 weeks x 4 doses, then Q9W) is given IM with EP by CELLECTRA® 2000 with cemiplimab (350 mg IV Q3W). RT is given as 40 Gy over 3 weeks. TMZ is given with radiation (all patients), and adjuvantly (Cohort B only). RESULTS: Fifty-two subjects enrolled: 32 in Cohort A; 20 in Cohort B. 35% women; median age 60 years (19–78 years). The adverse event profile is consistent with single-agent (INO-5401, INO-9012, EP and cemiplimab) reported events. OS at 12 months was 84.4% (Cohort A) and 85% (Cohort B). OS at 18 months in Cohort A is 50% (95% CI 31.9 - 68.1); median OS is 17.9 months (14.5 - NR); Cohort B OS18 and median OS will be presented. Tumor gene transcripts at diagnosis confirmed expression of INO-5401 antigens. Peripheral immune responses following INO-5401 revealed antigen-specific T cell responses by Interferon gamma ELISpot and flow cytometry, including cytokine production and expansion of antigen specific CD8+T cells with lytic potential. CONCLUSIONS: INO-5401 + INO-9012, a novel DNA plasmid immunotherapy, demonstrates acceptable risk/benefit and generates robust systemic immune responses to encoded tumor antigens when administered with cemiplimab and RT/TMZ in newly diagnosed GBM patients. Overall survival is encouraging. Clinical trial information: NCT03491683.